Migration of Lung Resident Group 2 Innate Lymphoid Cells Link Allergic Lung Inflammation and Liver Immunity - Mathä, Laura; Romera-Hernández, Mónica; Steer, Catherine A.; Yin, Yi Han; Orangi, Mona; Shim, Hanjoo; Chang, ChihKai; Rossi, Fabio M.; Takei, Fumio (Frontiers in Immunology, 2021)
Group 2 innate lymphoid cells (ILC2s) are tissue resident in the lung and activated by inhaled allergens via epithelial-derived alarmins including IL-33. Activated ILC2s proliferate, produce IL-5 and IL-13, and induce eosinophilic inflammation. Here, we report that intranasal IL-33 or the protease allergen papain administration resulted in increased numbers of ILC2s not only in the lung but also in peripheral blood and liver. Analyses of IL-33 treated parabiosis mice showed that the increase in lung ILC2s was due to proliferation of lung resident ILC2s, whereas the increase in liver ILC2s was due to the migration of activated lung ILC2s. Lung-derived ILC2s induced eosinophilic hepatitis and expression of fibrosis-related genes. Intranasal IL-33 pre-treatment also attenuated concanavalin A-induced acute hepatitis and cirrhosis. These results suggest that activated lung resident ILC2s emigrate from the lung, circulate, settle in the liver and promote type 2 inflammation and attenuate type 1 inflammation.